Back Cover: The DiPPro Approach: Synthesis, Hydrolysis, and Antiviral Activity of Lipophilic d4T Diphosphate Prodrugs (ChemMedChem 4/2014). Issue 4 (April 2014) - Schulz, Tilmann; Balzarini, Jan; Meier, Chris
<x xml:space="preserve">Abstract</x> The back cover picture shows how a masked precursor of a nucleoside diphosphate (DiPPro) is taken up by a virus‐infected cell due to its high lipophilicity. Intracellularly, the bioreversible masking units are enzymatically cleaved to the delivery of the diphosphate (B=base, S=sugar, P=phosphate). After conversion into the triphosphate, the nucleotide is able to inhibit viral replication by blocking reverse transcriptase (RT). For further details, see the Full Paper by Chris Meier et al. on p. 762 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>